Efforts to Improve Student Learning Outcomes in Natural Science Learning Using the Drill Method at MIN 32 Aceh Besar - Hasriana (Journal of Indonesian Primary School, 2025)
This study aims to determine the improvement in learning outcomes of class V-B students of MIN 32 Aceh Besar in the 2020/2021 academic year in studying Natural Sciences on the subject of animal classification based on their food types through the drill method. This classroom action research was conducted for 3 months, namely from September to November 2020. The research method used was classroom action research consisting of 2 cycles. The subjects of the study were 19 students of class V-B MIN 32 Aceh Besar in the 2020/2021 academic year. Data analysis using comparative descriptive analysis techniques by comparing initial conditions with the results achieved in each cycle, and qualitative descriptive analysis of observation results by comparing observation results and reflections in cycle I and cycle 2. Where student learning completeness increased in the pre-cycle, students who completed learning were 7 people (36.8%) and those who did not complete were 12 people (63.2%), in cycle I, students who completed learning were 11 people (57.9%) and those who did not complete were 8 people (42.1%) and in cycle II, students who completed learning became 17 people (89.5%) and those who did not complete were 2 people (10.5%), the percentage of student activity in cycle I was 50.5% and was classified as lacking, the percentage of teacher PBM ability was 65% and was classified as lacking. In cycle II, the percentage of student activity reached 85.7% and was classified as good, while the teacher's learning management ability had a percentage of 95% and was classified as very good. Thus, most of the students in class V-B MIN 32 Aceh Besar experienced an increase in learning outcomes in the material on animal classification based on their type of food.